Religious education and social literacy: the 'white elephant' of Australian public education - Davies, Tanya (British Journal of religious education, 2019)
As a result of globalisation, the boundaries that once limited the trade of ideas and culture have largely dissolved. In Australia, the fruits of intercultural exchange have largely been enjoyed, yet this expansion of Australian interaction with diverse Others has posed a perceived threat to some. This parallel expansion and contraction of cultural engagement demonstrates the need for Australia to represent diversity more adequately as a part of our society. A central point of tension in this discussion is religion. This paper reports on a study that explored the question: Why is it so hard to talk about religion in public classrooms? This narrative inquiry attempts to unpack some of the challenges facing Australian educators at present. This study brings out the conflicting priorities and pressures of the secular system against student needs and puts forward an argument for the development of social literacy education that addresses education about religion in Victorian public schools.